Ankle pump exercise to reduce edema in congestive heart failure - Vitryya Dwi Kusumawati; Indriana Noor Istiqomah; Mashuri; Anggia Astuti; Laili Nur Azizah (KHD-Production, 2025)
Fluid overload in the circulatory system is a common symptom of Congestive Heart Failure (CHF), often leading to the nursing problem of hypervolemia, characterized by pulmonary and lower extremity edema. One intervention that may reduce edema is the ankle pump exercise. This study aimed to evaluate changes in edema in a CHF patient with hypervolemia following the implementation of the ankle pump exercise. This study employed a descriptive method using a case study approach. The participant was a 67-year-old male diagnosed with CHF, presenting with apathetic consciousness, jugular venous pressure (JVP) of 9 cmH₂O, positive hepatojugular reflux, and lower extremity edema at grade +2. The intervention involved passive dorsiflexion and plantarflexion of the ankle for 5–10 minutes, once daily, over six consecutive days in a semi-Fowler’s position. A reduction in edema was observed from grade +2 to 0. Evaluation criteria showed improvement in paroxysmal nocturnal dyspnea and jugular vein distension (JVP reduced to 6 cmH₂O), with no tachycardia (pulse 80 bpm). However, dyspnea, orthopnea, and the S3 heart sound remained present. Ankle pump exercise may be considered as a supportive nursing intervention to reduce lower extremity edema in CHF patients with hypervolemia. However, as this is a single-case study, the findings cannot be generalized to other cases. Larger studies are needed to validate these outcomes.